Blob dynamics in the TORPEX experiment: a multi-code validation. (22nd January 2016) - Riva, F; Colin, C; Denis, J; Easy, L; Furno, I; Madsen, J; Militello, F; Naulin, V; Nielsen, A H; Olsen, J M B; Omotani, J T; Rasmussen, J J; et al.
Abstract: Three-dimensional and two-dimensional seeded blob simulations are performed with five different fluid models, all based on the drift-reduced Braginskii equations, and the numerical results are compared among themselves and validated against experimental measurements provided by the TORPEX device (Fasoli et al 2006 Phys. Plasmas 13 055902). The five models are implemented in four simulation codes, typically used to simulate the plasma dynamics in the tokamak scrape-off layer, namely BOUT++ (Dudson et al 2009 Comput. Phys. Commun .180 1467), GBS (Ricci et al 2012 Plasma Phys. Control. Fusion 54 124047), HESEL (Nielsen et al 2015 Phys. Lett . A379 3097), and TOKAM3X (Tamain et al 2014 Contrib. Plasma Phys .54 555). Three blobs with different velocities and different stability properties are simulated. The differences observed among the simulation results and the different levels of agreement with experimental measurements are investigated, increasing our confidence in our simulation tools and shedding light on the blob dynamics. The comparisons demonstrate that the radial blob dynamics observed in the three-dimensional simulations is in good agreement with experimental measurements and that, in the present experimental scenario, the two-dimensional model derived under the assumption of is able to recover the blob dynamics observed in the three-dimensional simulations. Moreover, it is found that an accurate measurement of the blob temperature is important to perform reliable seeded blob simulations.